The ditchdigger's daughters : a black family's astonishingsuccess story - Thornton, Yvonne S.; Coudert, Jo (New York, N.Y., U.S.A. : Plume, 1995)
A biography by a New Jersey doctor tells how her parents, who held down multiple jobs and transmitted strong values to their six daughters, inspired them to reach success.
70392
Keywords: Thornton family; Thornton, Yvonne S. -- Family; African Americans -- Biography -- New Jersey; Success -- New Jersey; New Jersey -- Biography